PENANGANAN PEMBIAYAAN BERMASALAH DALAM PELAKSANAAN AKAD DENGAN PRINSIP MURABAHAH DI BANK MUAMALAT INDONESIA CABANG YOGYAKARTA - WIRATMANTO WIRATMANTO (Jurnal Media Hukum, 2012)
Fakultas Hukum, , Jalan Lingkar Selatan, Tamantirto, Kasihan, Bantul, Yogyakarta,55183 Indonesia. ABSTRACT The aim of this research is to understand the aspect of settlement law of financial problem, handling of financial problem and law attainment used for the solution of financial problem within the implementation of principally murabahah covenant in Indonesian Muamalat Bank, particularly in Yogyakarta. The final conclusion for this research is the handling of financial problem within the implementation of principally murabahah covenant in Indonesian Mualamat Bank through redemption and settlements acts of financial problem. The redemption act is done by rescheduling. Besides that, reconditioning and restructuring are also conducted. Law attainment used in the settlement of financial problem within the implementation of principally murabahah covenant in Indonesian Muamalat Bank is by conducting bank internal settlement that is discussion to reach common agreement. Other than that, the settlement phases that can be done are denunciation to Bank of Indonesia, mediation even though for the settlement through that bank, arbitration, of which it is bonding and last, through BASYARNAS so that if there is an in-obedient side, they can demand for flat execution to Religious Court, litigation (Religious Court). The prosecution can be directly filed to Religious Court based on Act Number. 3 of The Year 2006.